(3QSGdI GdZaQGf ef GdecK HMQGfs ((3eSLO GdLHQhfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd hai cd eKhi hEQJMGd GdefRg Yf eJTGHgg GdCeKGd hGdCTcGd GdeJYGdi Yf GdJeKjd ai GdMS hGdhge hGdNjGd CeG HYO aEffi Mjf Gdchf HMQGf Sfg SHY hKeGf hYTQjf hSJ eGFI CdReJ faSi GdCfbWGY Yf eNGdWI CgdgG s
(3BNQgG (B:s
(3aGSO EYJbGOg GdeYQha ai dMf NWGHg gh hSGFQ CUMGHg cHQJ cdeI JNQL ef CahGgge Cf jbhdhf EdG cPGH SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJhMjO hGdedd hGdfMds